2009
DOI: 10.3168/jds.2008-1877
|View full text |Cite
|
Sign up to set email alerts
|

Chromium supplementation and substitution of barley grain with corn: Effects on performance and lactation in periparturient dairy cows

Abstract: Thirty-two multiparous Holstein cows were used to investigate the effects of chromium-l-methionine (Cr-Met) supplementation and dietary grain source on performance and lactation during the periparturient period. Cows were fed a total mixed ration consisting of either a barley-based diet (BBD) or a corn-based diet (CBD) from 21 d before anticipated calving through 28 d after calving. The Cr-Met was supplemented at dosages of 0 or 0.08 mg of Cr/kg of metabolic body weight. The study was designed as a randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 32 publications
8
46
3
Order By: Relevance
“…Reduced NEFA alongside the increased peripheral glucose concentrations and enhanced milk secretion suggests that the Cr improved nutrient availability at times of high metabolic demands. Increased milk fat percentage and total solids in the present findings are inconsistent with those obtained by Hayirli et al [28] and Nikkhah et al [24] but are in disagreement with the result of McNamara and Valdez [23], Smith et al [21], and Sadri et al [18]. Hayirli et al [28] reported that increasing Cr supplementation caused a quadratic increase in milk fat and lactose yield.…”
Section: Productive Performancecontrasting
confidence: 72%
See 1 more Smart Citation
“…Reduced NEFA alongside the increased peripheral glucose concentrations and enhanced milk secretion suggests that the Cr improved nutrient availability at times of high metabolic demands. Increased milk fat percentage and total solids in the present findings are inconsistent with those obtained by Hayirli et al [28] and Nikkhah et al [24] but are in disagreement with the result of McNamara and Valdez [23], Smith et al [21], and Sadri et al [18]. Hayirli et al [28] reported that increasing Cr supplementation caused a quadratic increase in milk fat and lactose yield.…”
Section: Productive Performancecontrasting
confidence: 72%
“…No effect of dietary Cr supplementation on DMI was reported by Kumar et al [17] who fed 0.5, 1.0, and 1.5 mg of inorganic Cr/kg DM to summer-exposed buffalo calves. Similarly, dietary addition of 1.6 mg of Cr/kg of DM in Holstein cows did not exert any effect on DMI [18]. Reports of a similar trend were given by other researchers [19][20][21][22].…”
Section: Dry Matter Intake and Body Condition Scoresupporting
confidence: 66%
“…Sadri et al [9] also reported no change in nutrient intake in 0.8 mg Cr-methionine/kgW 0.75 supplemented periparturient cows. Similarly, Rikhari et al…”
Section: Discussion Nutrients Intake and Milk Yieldmentioning
confidence: 92%
“…Moreover, even rations containing Cr concentrations satisfying the need during a normal production period can become deficient in critical situations, such as advanced pregnancy, parturition, onset of lactation, weaning, and transport. Several researchers reported increased nutrient intake [7,8], whole tract apparent digestibility [9], and greater milk production [7,10] as a result of Cr supplementation. Cr supplementation decreased insulin concentration and increased glucose concentration and glucose insulin index in relation to cows not receiving Cr [11].…”
Section: Introductionmentioning
confidence: 99%
“…In a constant level of forage particle size (theoretical length cut of 30 mm), however, it is not known whether changing diet fermentability (using grains different in expected ruminal fermentation) when supplemented with unsaturated oil would affect lactational performance and eating and ruminating activities. Most experiments that have considered the effect of grain type and fat supplementation of the diet have used a type of rumen-inert fat (Sadri et al, 2009;Nasrollahi et al, 2012). Therefore, it remains unclear how performance and behavior of dairy cows would be influenced by changing fermentability of diets supplemented with unsaturated oil.…”
Section: Introductionmentioning
confidence: 99%